2020
DOI: 10.3390/ijerph17113999
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Impacts of Particulate Matter Levels on Bike Sharing in Seoul, South Korea

Abstract: Bike sharing is increasingly attracting more riders in cities around the world for its benefits regarding the urban environment and public health. The public bike sharing program of Seoul, South Korea, first launched in October 2015, is now widely spread around the city and serves more than 27,000 riders daily. However, concerns are being raised as rising air pollution levels in Seoul, represented by particulate matter (PM) levels, in recent years may negatively discourage citizens from using bike sharing. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…In this study, adjusting outdoor activity based on air quality was found to be associated with frequent bike share trips for dual or triple-purpose. Regarding the impact of particulate matter (PM) levels on bike share, one study conducted in Seoul, South Korea, revealed that PM 10 and PM 2.5 levels had negative impact on bike share use, particularly in winter and spring [ 42 ]. Another study reviewed seven studies on air quality and physical activity and concluded that poor air quality was related to lower odds of physical activity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, adjusting outdoor activity based on air quality was found to be associated with frequent bike share trips for dual or triple-purpose. Regarding the impact of particulate matter (PM) levels on bike share, one study conducted in Seoul, South Korea, revealed that PM 10 and PM 2.5 levels had negative impact on bike share use, particularly in winter and spring [ 42 ]. Another study reviewed seven studies on air quality and physical activity and concluded that poor air quality was related to lower odds of physical activity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a goodness-of-fit analysis, and subsequently, determined that a negative binomial regression analysis is most suitable for this data. A negative binomial regression is a statistical model used in various fields and has been proven to be highly effective in many existing studies in similar fields [24]. As mentioned previously, we used PV as the dependent variable and the microclimatic factors (temperature, precipitation, and PM10) as independent variables.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Changes in daily life due to PM mainly appear in the form of a decrease in various urban activities, such as walking, leisure, labor, and consumption [40,41]. In Korea, studies have also reported that PM affects PV [42], bicycle use [24], and outdoor leisure activities [43].…”
Section: Previous Perspectives On Microclimatic Conditions and Enviromentioning
confidence: 99%
See 1 more Smart Citation
“…Usage initially continued to increase during the summer (June to August), but declined in August. In autumn (September-November), bike sharing was the most used, with up to 60,000 trips per day, but it dwindled towards November [49].…”
Section: Kim H (2020)mentioning
confidence: 99%